Identification of Pulse Discharge Parameters in Water for Reservoir Resonance Transform Device. Issue 1 (1st December 2022) - Kang, Zhongjian; Shao, Zaikang; Gao, Chong
Abstract: The reservoir resonance transform device is applied to unconventional shale gas stimulation. To achieve the purpose of resonance stimulation, the discharge frequency is dynamically corresponding to the natural frequency of the reservoir. However, the discharge parameters under the same conditions differ in the resonance process. It is hard to analyze the real-time change of reservoir frequency precisely. Therefore, the identification of pulse discharge parameters in water is extremely important. In this paper, an equivalent circuit model of pulse discharge in water is established to analyze the time-varying resistance. The Kalman filter makes the discrete resistance data continuous and reduces the interference caused by the random discharge. Meanwhile, the data error analysis is carried out. The results show that the variance of pulse discharge resistance in water based on the Kalman filter is less than 0.528 compared with the experiment value, so the identified resistance obtained by this method can be used in the study of resonant discharge in the same frequency.